EVALUATION OF AN ESP TEXTBOOK FOR THE STUDENTS OF FASHION DESIGN - Hasibuan, Roslina; Fithriani, Rahmah (Universitas Islam Sumatera Utara (UISU), 2022)
Evaluation is a crucial step in the process of enhancing the quality of educational materials through the design of new content. The evaluation of textbooks in English Language Teaching can be conducted using a variety of techniques. Adapted from Cunningsworth and Kusel (1991) and Skierso (1991), this study utilized checklist instruments to determine whether or not a textbook is appropriate for use. This study provides an overview of ELT textbook evaluation, with a particular emphasis on the use of a checklist. It aimed to assess the suitability of a specific textbook for an ESP course for fashion design students. According to the findings of this study, 90 percent of respondents agree this book is excellent based on its general attributes and 93 percent agree based on its learning and teaching content. The presentation above suggests that this book can be used for ESP courses by fashion design students. However, the book does not come without any weaknesses, which include the absence of a book for teachers and the absence of pair and group exercises.